2012
DOI: 10.1158/0008-5472.can-11-3666
|View full text |Cite
|
Sign up to set email alerts
|

CD24 Is an Effector of HIF-1–Driven Primary Tumor Growth and Metastasis

Abstract: Hypoxia drives malignant progression in part by promoting accumulation of the oncogenic transcription factor HIF-1α in tumor cells. Tumor aggressiveness also relates to elevation of the cancer stem cell-associated membrane protein CD24, which has been causally implicated in tumor formation and metastasis in experimental models. Here we link these two elements by showing that hypoxia induces CD24 expression through a functional hypoxia responsive element (HRE) in the CD24 promoter. HIF-1α overexpression induced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 48 publications
4
111
0
Order By: Relevance
“…Two previously published CD24 promoter sequences (42,43) showed considerable mismatch between each other and a partial promoter from GenBank. Therefore we cloned and sequenced the CD24 promoter from several distinct human cell lines to identify a common sequence for our studies as described (44). The sequences can be found in GenBank with the following accession numbers: UM-UC-3 CD24 promoter, JN565036; J82 CD24 promoter, JN565037; LNCaP CD24 promoter, JN565040; LuL-2 CD24 promoter, JN565041; and EJ CD24 promoter, JN565042.…”
Section: Methodsmentioning
confidence: 99%
“…Two previously published CD24 promoter sequences (42,43) showed considerable mismatch between each other and a partial promoter from GenBank. Therefore we cloned and sequenced the CD24 promoter from several distinct human cell lines to identify a common sequence for our studies as described (44). The sequences can be found in GenBank with the following accession numbers: UM-UC-3 CD24 promoter, JN565036; J82 CD24 promoter, JN565037; LNCaP CD24 promoter, JN565040; LuL-2 CD24 promoter, JN565041; and EJ CD24 promoter, JN565042.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we identified the differentiation marker CD24 and the apoptotic protein PAWR as direct SRC1/ HOXC11 suppression targets. CD24 has been identified as a transcriptional target gene for hypoxia-inducible factor-1a (HIF-1a) and has been linked to HIF-1a-mediated tumor growth in both primary and metastatic tumors (25). Functions of CD24, however, may depend on the cellular context, in particular with regard to endocrine cancer.…”
Section: Src-1 Utilizes Jmjd2c To Silence Cd24 and Pawrmentioning
confidence: 99%
“…[34][35][36] To some extent, low oxygen tension is critical for cancer stem cell maintenance and therefore responsible for fatal tumor progression and reoccurrence. 37,38 A past study has shown that culturing of mouse and human fibroblasts under hypoxia can improve the reprogramming efficiency of the induced pluripotent stem cell (iPS). 39 It has also been reported that stem cells possess low level of global methylation compared with terminally differentiated cells.…”
Section: Introductionmentioning
confidence: 99%